2016
DOI: 10.17061/phrp2631634
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking by adult emergency department patients in Australia: a point-prevalence study

Abstract: Objectives and importance of study: Tobacco smoking is the leading single cause of preventable death. International findings suggest that rates of smoking are higher among emergency department (ED) patients than the general population, suggesting that the ED may be a strategic location in which to initiate smoking cessation programs. We aimed to determine the prevalence of smoking among adult ED patients in Australia, their desire for smoking cessation and preferred methods of cessation. Study type: Point-prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…A hospital population comprising 399 Russian cancer patients found that 41.6% were smokers 32 , indicating a higher prevalence compared to the general population, however smoking is a well-known significant risk factor for cancer. Also, among 335 Australian ED patients smoking prevalence was found to be 23%, compared to 18% in the general population 33 . One explanation for the similar prevalences in our study and the general Russian population might be that our hospital population is older compared to the general population described in GATS, which might be due to the negative impact of tobacco use on individual life expectancy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A hospital population comprising 399 Russian cancer patients found that 41.6% were smokers 32 , indicating a higher prevalence compared to the general population, however smoking is a well-known significant risk factor for cancer. Also, among 335 Australian ED patients smoking prevalence was found to be 23%, compared to 18% in the general population 33 . One explanation for the similar prevalences in our study and the general Russian population might be that our hospital population is older compared to the general population described in GATS, which might be due to the negative impact of tobacco use on individual life expectancy.…”
Section: Discussionmentioning
confidence: 93%
“…Also, GATS showed that older adults generally believe that smoking causes serious illnesses 5 , which again might explain why fewer older adults smoke. The patients in the younger age groups (18-40 and 41-60 years) have a much higher prevalence of smokers compared to the younger age groups in the general population (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) and 45-64 years) 5 , indicating that smoking might have been a contributing factor for somatic illness in the younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Representing a key risk factor for deaths due to ischaemic heart disease, stroke and cancer, tobacco smoking kills approximately 6 million people globally each year. 1 2 Holding the potential to damage nearly every organ system in the human body, tobacco smoking accounts for 7.8% of the total burden of disease in Australia. 1 2 Despite this, 14% of adults aged 18 years and over smoked daily in 2017–2018.…”
Section: Introductionmentioning
confidence: 99%
“… 1 2 Holding the potential to damage nearly every organ system in the human body, tobacco smoking accounts for 7.8% of the total burden of disease in Australia. 1 2 Despite this, 14% of adults aged 18 years and over smoked daily in 2017–2018. 2 3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation